How Inflation Could Moderate The Effect of Financial Ratio on Stock Return - Dewi, Luh Gede Sintha; Merawati, Luh Komang; Tandio, Daniel Raditya (Ratio : Reviu Akuntansi Kontemporer Indonesia, 2023)
Stock return is something that is expected to be obtained by all investors who invest in the capital market. Financial stock returns will occur if the company’s profits increase which makes the company distribute dividends. This study aims to test and obtain empirical evidence of the effect of Return on Equity, Debt to equity ratio, and Dividend Yield on stock returns of consumer goods companies listed on the Indonesia Stock Exchange. The research population is manufacturing companies listed on the IDX in 2019-2021. The sample in this study were 46 consumer goods companies which were determined based on purposive sampling method. The analytical tool used to test the hypothesis is moderate regression analysis. The results showed that Return on Equity and Dividend Yield had a positive effect on stock returns. Meanwhile, Debt to equity ratio has a negative effect on stock returns. Likewise, in inflation as a moderating variable where on the variable Return on Equity and Debt to equity ratio inflation does not moderate the effect of Return on Equity and Debt to Equity Ratio on Stock Returns while on the Dividend Yield variable inflation weakens the effect of Dividend yield on Stock Returns. Future research can develop this research by using other variables that in theory have an influence on stock returns, such as interest rates.